2017
DOI: 10.1186/s12871-017-0405-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of increased body mass index in outcomes of sepsis: a systematic review and meta-analysis

Abstract: BackgroundThe role of increased body mass index (BMI) in sepsis is controversial. We aimed to evaluate the associations between overweight (25 kg/m2 < BMI ≤ 29.9 kg/m2), obese (30 kg/m2 < BMI ≤ 39.9 kg/m2) and morbidly obese (BMI > 40 kg/m2) BMIs and outcomes in septic patients.MethodsWe searched the PubMed, Embase, Web of Science, Cochrane Library and ClinicalTrials.gov databases for studies published by December 1, 2016. Electronic database searches yielded 3713 articles, eight of which were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 49 publications
7
67
1
5
Order By: Relevance
“…Different from these findings in animal obesity models, two recent systematic reviews of observational clinical studies and a retrospective analysis of a large patient database found that obese body mass indices (BMI) appeared to increase survival in septic patients [13][14][15]. Preclinical and clinical results may differ for several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from these findings in animal obesity models, two recent systematic reviews of observational clinical studies and a retrospective analysis of a large patient database found that obese body mass indices (BMI) appeared to increase survival in septic patients [13][14][15]. Preclinical and clinical results may differ for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…is point is highlighted by conflicting data regarding obesity's effects on mortality in patients with bacterial infection and sepsis or viral influenza, two common reasons for ICU admission. Although several individual studies suggest that obesity worsens or has no impact on survival in patients with sepsis, two recent systematic reviews and meta-analyses both reported that overweight or obese body mass indices (BMIs) were paradoxically associated with improved outcomes in sepsis [11][12][13][14][15]. By contrast, two other systematic reviews and metaanalyses and a retrospective analysis of a large patient database found that for patients with influenza pneumonia, obesity increased the risk of either a combined endpoint of ICU admission and death or death alone [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the visceral fat (VAT) accumulation detected by CT scan was a risk factor for poor prognosis of sepsis. Sepsis patients with a high ratio of VAT area to the subcutaneous fat (SAT) area had an increased risk of death and organ damage [17] . In future, more detailed and rigorous studies should be designed to clarify the relationship between sepsis and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In sepsis cases overweight, but not obesity, was associated with lower risk of mortality. 6 Other cohort data have suggested that overweight and obesity is associated with higher risk of respiratory and skin infections, 14 higher 30 day mortality risk after detection of blood borne bacterial infection, 15 whilst protective against viral and fungal infections. 14 The aim of the present study was to examine associations between multiple lifestyle risk factors, obesity (both from BMI and waist measures) and infectious disease mortality in a large general population cohort.…”
Section: Introductionmentioning
confidence: 99%